Characteristics of gas-turbine engines with air turbine heatutilizing installations - Кучеренко, О.С.; Мовчан, С.Н.; Филоненко, А.А.; Чобенко, В.Н.; Кузнецов, В.В.; Шевцов, А.П. (Eastern-European Journal of Enterprise Technologies, 2010)
Results of research gas turbine (GT) with air heat recovery turbine unit (AHRTU) in ranges of air temperature in inlet of the turbine from 573 up to 873 K and a degree of pressure ratio in the compressor from 2,5 up to 12 are presented. Basic parameters AHRTU for use with serial GT various firms over the range capacities from 16 up to 25 MW are determined.